A Hidden Epistemology: The Deterritorialisation of Theology in L'Écriture de l'histoire (1970-1975) - Freijomil, Andrés Gabriel (2025)
How are fields of historiographical specialisation constructed? How can we perceive and trace the intersection between institutional problems and the epistemological implications of disciplines at a time when they are marking out their ruptures? These are the issues that Michel de Certeau considered in 1970 in order to deterritorialize theology from the broad hegemonic ocean represented at that time by historiography and, in particular, social history. To do this, Certeau has regularly used a material tactic of re-employing texts (especially the rewriting of articles into book chapters) and a precursory epistemological toolkit from the human sciences.